Lessons in Engagement from a Malay Classic: The Translation of Syair Siti Zubaidah Perang China - Lalita Sinha (Kajian Malaysia, 2010)
Poetry has always played an important role in sustaining languages, as well as in conveying both the "outward" or literal and the "inward" or hidden meaning of words. The classic poem from the oral tradition of the Malay world, Syair Siti Zubaidah Perang China, conveys the nature of relationships between different cultures and traditions. One aspect of this relationship is the apparent conflict and war between the people of Kembayat Negara (or Malay-Muslims) and those of China (the Chinese tradition). However, in the process of translation of the text from Malay to English, a harmonious engagement between the Malay and the Chinese cultures has been unravelled. The contention is that through a hermeneutical reading of the text, and through observation of the exacting demands of literary translation, rich reflections of acceptance of "the other" are found, at a level that might otherwise have remained hidden. By revealing the meanings beyond the apparent theme of war and conflict, this paper offers a model for the translation of classical Malay poetry